Dansyl-modified carbon dots with dual-emission for pH sensing, Fe3+ ion detection and fluorescent ink. Issue 61 (7th October 2020) - Tian, Hua; Dai, Yongcheng; Fu, Wenzhe; Liu, Haifang; Li, Mengting; Lv, Meiyuan; Yin, Xueqiong
Abstract : This work provided a new strategy for developing a multifunctional fluorescence platform which had potential in the detection of pH and metal ions, as well as showing promising application in the anti-counterfeiting field. Abstract : In this work, a multifunctional ratiometric fluorescence (FL) nanohybrid (CSCDs@DC) was synthesized from chitosan based carbon dots (CSCDs) and dansyl chloride (DC) at room temperature. The CSCDs@DC revealed strong FL intensity, great stability and excellent anti-photobleaching properties. Herein, CSCDs@DC was responsive to pH value in the range of 1.5–4.0 and exhibited color-switchable FL properties between acidic and alkaline environments. In addition, CSCDs@DC showed good selectivity and sensitivity towards Fe 3+ ions. A good linear relationship for the Fe 3+ ion detection was obtained in the range from 0 μM to 100 μM, with a detection limit of 1.23 μM. What's more, CSCDs@DC can be used as a fluorescent ink. It expressed superior optical properties after 3 months of storage or continuous exposure to UV light for 24 h. This study suggested that CSCDs@DC had potential in the detection of pH and metal ions, as well as showing promising application in the anti-counterfeiting field.